2017
DOI: 10.1371/journal.pone.0189505
|View full text |Cite
|
Sign up to set email alerts
|

Is quality of life different between diabetic and non-diabetic people? The importance of cardiovascular risks

Abstract: BackgroundTo analyse and compare the impact of cardiovascular risk factors and disease on health-related quality of life (HRQoL) in people with and without diabetes living in the community.MethodsWe used data of 1,905 people with diabetes and 19,031 people without diabetes from the last Spanish National Health Survey (years 2011–2012). The HRQoL instrument used was the EuroQol 5D-5L, based on time trade-off scores. Matching methods were used to assess any differences in the HRQoL in people with and without dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…The presence of comorbid hypertension was not significantly associated with HRQoL for both sexes in this study. This is in contrast with reports from studies in Greece [ 36 ], and Spain [ 38 ], where presence of hypertension and other comorbidities was associated with lower HRQoL scores. However, in this study, subjects’ systemic blood pressures were found to be indirectly correlated with HRQoL.…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of comorbid hypertension was not significantly associated with HRQoL for both sexes in this study. This is in contrast with reports from studies in Greece [ 36 ], and Spain [ 38 ], where presence of hypertension and other comorbidities was associated with lower HRQoL scores. However, in this study, subjects’ systemic blood pressures were found to be indirectly correlated with HRQoL.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, diabetic patients with no other vascular risk factors or vascular disease have a similar HRQoL to that of the general non-diabetic population, after adjusting for covariates. However, when the diabetic patient has several risk factors or has developed vascular disease, the HRQoL decreases significantly [41].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Both CVD and acute CV events have a major clinical impact and negatively affect patients' quality of life. 11 The Food and Drug Administration requires concrete evidence regarding CV safety when evaluating new treatments for diabetes. This evidence includes an assessment of major adverse cardiovascular events (MACE), that is, non-fatal stroke, non-fatal acute myocardial infarction (AMI) and CV death.…”
Section: Significance Of This Studymentioning
confidence: 99%
“… 7–10 Both CVD and acute CV events have a major clinical impact and negatively affect patients’ quality of life. 11 …”
Section: Introductionmentioning
confidence: 99%